Linking Emotional Intelligence and Transformational Leadership: An empirical study of the Portuguese Technological Sector - Moreira, Joana Filipa Amorim (2022)
This study aims to analyze the relationship between emotional intelligence, including its dimensions, and transformational leadership in Portuguese companies from the technology sector. In this sense, we reviewed the literature on emotional intelligence, transformational leadership and the linkage between themes. An empirical study was conducted using an online questionnaire to adopt a quantitative methodological approach. 180 responses were obtained from executive directors of companies in the mentioned sector. Data analysis was performed using the structural equation model (SEM). The results demonstrated a positive and significant relationship between three of emotional intelligence dimensions’ and transformational leadership, more specifically, between self-emotion appraisal (SEA), other’s emotion appraisal (OEA) and the use of emotions (UA), and between transformational leadership. However, the relationship between emotion regulation (ER) and transformational leadership was not supported. This study differs from the others as it seeks to establish relationships between emotional intelligence dimensions’ and transformational leadership rather than treating the emotional intelligence’s construct as a whole. Therefore, considering the scarce literature relating to the mentioned constructs fills the literature’s lack. Its applicability in the Portuguese technological sector is also an innovative factor.